Geometric and kinematic analysis of faults bordering the Andaman sea continental shelves: a 3D seismic case study - Guo, Meng; Luan, Xiwu; Zhang, Huixing; He, Bingshou (Frontiers in Earth Science, 2023)
To clarify the tectonic evolution of M15 block in the Andaman Sea, we perform a delicate study of fault geometry and dynamics using a 3D seismic data. The data reveal eight sequence interfaces from the Early Oligocene to the Quaternary, large scale and multi angle extensional strike-slip faults, and a series of normal faults. The two large scale faults F1 and F2 start in the Eocene and end in the Quaternary, controlling the regional structure. The NNE-SSW strike-slip F1 fault belongs to the South Sagaing fault and the NNE-SSW strike-slip F2 is the eastern Andaman fault, the strike-slip movement of which are controlled by the impact of the collision between the Indian plate and the Eurasian plate. Through the analysis of the fault development history by the method of the ancient drop and the growth index, we find that most of the large or secondary scale faults reach the maximum drop and growth index in the Miocene, indicating that the Miocene is a significant period of plate collision enhancing and faults generating. The regional stress field is dominated by E-W tension. The continental crust has expanded rapidly from the Oligocene to the Miocene which results in the rapid subsidence of the crust. This regional stress intensity becomes weak after the Miocene. The activities of the faults caused a large difference in terrain height between the west and the east in the study area, forming a pattern of the western depression and the eastern terrace. Many NNE-SSW, NE-SW or NEE-SWW trend strike-slip faults and minor faults develop in the Miocene. It echoes the event that the convergence and subduction of the Indian plate from SW to NE direction led to the right rotation and N-NNE strike-slip of the West Myanmar block in the Miocene, thus forming a regional large strike-slip fault. All of the faults affect the structure of the region.